Impacts of landscape changes on soil carbon storage in fragments of the Cerrado biome in central-western São Paulo state - Alexandre, Lucas Franhani (2025)
In Brazil, land use and land cover changes alone account for 36.1% of greenhouse gas (GHG) emissions. In this context, soil plays a critical role acting either as a source or sink of carbon (C) to atmosphere. Multiple benefits arise from soil C storage, including contributions to food production, ecosystem habitat preservation, flora and fauna dissemination, and climate regulation. Therefore, monitoring soil functions and understanding C cycling amongst reservoirs is essential for sustaining life on Earth. The Intergovernmental Pannel of Climate Change (IPCC) has promoted various initiatives to assess inventories and monitor soil carbon stocks (CS) worldwide, requiring data from up to 30 cm depth, and recommending, whenever possible, extending it to 1 meter. Although significant efforts have been made to understand fluxes and monitor variations, developing countries as Brazil still face data gaps and an uneven information distribution. Employing a multidisciplinary approach, we evaluate the impacts of human actions, compare two biome potentials, and refine metrics by using soil characteristics as indicators to bridge these data gaps. Our study site included an ecotone between Savanna and Atlantic Forest vegetation, as well as a portion of deforested land. A brief time-series analysis was conducted to assess vegetation dynamics and human activity impacts on the landscape. Soil samples were collected from 30 spatially distributed points using a Dutch auger, encompassing five intervals, up to 1m depth and totaling 150 samples. These samples were analyzed according to Brazilian procedures for macro and micronutrient content and particle size characterization. Additionally, samples were processed in an elemental analyzer connected to a mass spectrometer to determine carbon and nitrogen content and the isotopic composition of 13C and 15N. Bulk density was estimated for each point and depth interval using an equation of pedotransfer functions. Although Savanna and Atlantic Forest soils appeared similar at first glance, they exhibited distinct CS, showing less contents than reported in other studies. The African grass Urochloa decumbens, undergoing natural regeneration, demonstrated CS values comparable to those of native Savanna vegetation. Our findings highlight the potential of even exotic species contributing to carbon dioxide removal and if well managed, achieving higher values than native cover. Notably, our results indicate that 62 67 % of the carbon stored in Brazilian soils lies beyond the surface layer monitored under current IPCC metrics. These findings underscore the importance of deeper soil layers in carbon inventories and provide valuable insights for policymakers aiming to enhance climate mitigation strategies